Body mass-related predictors of the female athlete triad among adolescent athletes - Thralls, K. J.; Nichols, J. F.; Barrack, M. T.; Kern, M.; Rauh, M. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2016)
Early detection of the female athlete triad is essential for the long-term health of adolescent female athletes. The purpose of this study was to assess relationships between common anthropometric markers (ideal body weight [IBW] via the Hamwi formula, youth-percentile body mass index [BMI], adult BMI categories, and body fat percentage [BF%]) and triad components, (low energy availability [EA], measured by dietary restraint [DR], menstrual dysfunction [MD], low bone mineral density [BMD]). In the sample (n = 320) of adolescent female athletes (age 15.9± 1.2 y), Spearman`s rho correlations and multiple logistic regression analyses evaluated associations between anthropometric clinical cutoffs and triad components. All underweight categories for the anthropometric measures predicted greater likelihood of MD and low BMD. Athletes with an IBW >85% were nearly 4 times more likely to report MD (OR = 3.7, 95% CI [1.8, 7.9]) and had low BMD (OR = 4.1, 95% CI [1.2, 14.2]). Those in <5th percentile for their age-specific BMI were 9 times more likely to report MD (OR 9.1, 95% CI [1.8, 46.9]) and had low BMD than those in the 50th to 85th percentile. Athletes with a high BF% were almost 3 times more likely to report DR (OR = 2.8, 95% CI [1.4, 6.1]). Our study indicates that low age-adjusted BMI and low IBW may serve as evidence-based clinical indicators that may be practically evaluated in the field, predicting MD and low BMD in adolescents. These measures should be tested for their ability as tools to minimize the risk for the triad.